Bowel diseases and constipation in practice of the obstetrician and gynecologist - I. V. Kuznetsova; Yu. B. Uspenskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of review. To present up-to-date data on etiology, pathogenesis and treatment of constipation in women of various age groups and at combined gynecologic diseases.Summary. Prevalence of functional constipation in women is almost twice higher, than in men. Predisposition of women to constipation is predetermined by anatomic, physiological and hormonal factors. In obstetrical practice constipation is associated with pregnancy and postnatal period, inflammatory and noninflammatory gynecologic diseases. This review presents modern management approaches at this pathology from gynecological point of view.Conclusion. Disorders of intestinal function in women are interdisciplinary issue. At constipated female patients detection of intestinal dysfunction etiology and improvement of management, it is necessary to pay attention not only to gastroenterological symptoms, but also to possible relation of symptoms to menstrual cycle, reproductive status and gynecologic pathology. Constipation at gynecologic diseases require treatment because disorders of bowel function in the most cases complicate course of gynecologic disorder and reduces treatment response rate.